Degradation of a LDPE film applied as a greenhouse cover design material: the effect of ageing and mechanical modelling - Garzón, Eduardo; Ortiz Rodríguez, Isabel María; Castillo, José; Sánchez-Soto, Pedro José (Revista de la Construcción. Journal of Construction, 2018)
In this work, we studied the mechanical performance of an LDPE film (0.22 mm in thickness) used as a material in the design of greenhouse covers. We investigated the effects of ageing at different periods of its service life and applying chemical substance treatments used as pesticides on greenhouse crops and after breakage using mechanical traction. Numerical simulations were performed using the finite element method. For this purpose, one section of the complete geometry of the greenhouse cover and different load conditions (1-5 kPa) were considered for the modelling. The performance of the polymer was assumed to be linearly elastic to simplify the governing equations. The study demonstrated that the LDPE film used was no longer effective as a greenhouse cover film due to the degradation of its mechanical properties. It was shown that the general performance of this film was in the plastic zone and its performance was non-linear. The results deduced from the present study are of interest because they show the material failure process of greenhouse covers in relation to the degradation process.